Монгол төрийн сонгох уламжлалын тухай асуудалд - Болдбаатар, Жигжид; Ариунаа, Л. (Historia Mongolarum, 2003)
The chronology of history before the establishment of modern republican election can be classified into three six phase: the ancient state election rules of Mongol states, the election rules o f the Great Mongol Empire, the political election rules in fragmentation times, the election rules in the Manchu oppression times, the election rules in Bogdo khan’s Mongol state, and the premature condition before republican election system.